Search for vector-like T quarks using events with oppositely-charged lepton pairs and jets in proton-proton collisions at centre-of-mass energy of 13 TeV with CMS detector - Mendis, Dalath Rachitha Asanga (Kansas State University, 2019)
A search is performed for heavy vector-like top quark partner (T) with electric charge +2/3 by using proton-proton collision events from Large Hadron Collider (LHC) at a centre- of-mass energy of 13 TeV. The data corresponds to an integrated luminosity of 35.9fb−1 collected by the Compact Muon Solenoid (CMS) experiment during 2016. The production of this new hypothetical particle is assumed to be in pairs and strong interaction is responsible for such production mechanism. T quarks can decay to various combinations of third generation quarks and standard model bosons: T → bW, tZ, or tH, and hence the final states consist of pair of opposite-sign leptons consistent with coming from a Z boson and jets. No significant excess has been observed and hence 95% CL upper limits are obtained on TT production cross section by assuming different branching ratios. T quark mass values below 1280 GeV are excluded in case of 100% branching fraction for T → tZ.
Keywords: CMS; Vector-like quarks; Top partners; Vector-like top quarks